2017
DOI: 10.1177/0269216316685234
|View full text |Cite
|
Sign up to set email alerts
|

Rural end-of-life care from the experiences and perspectives of patients and family caregivers: A systematic literature review

Abstract: Articulation of the rural voice is increasing; however, there still remain limited published rural studies reporting on patient and family caregivers' experiences and perspectives on rural end-of-life care. Further research is encouraged, especially through national and international collaborative work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
1
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 60 publications
(437 reference statements)
9
55
1
20
Order By: Relevance
“…A number of these findings on the perceived role of GPs in providing EOL care and barriers they experience are comparable to those of previous studies [18,24,[36][37][38][39], including studies that have focused on urban GPs [40]. However, the current study indicated that many of these barriers appear to be more pronounced in rural versus urban contexts within Australia.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A number of these findings on the perceived role of GPs in providing EOL care and barriers they experience are comparable to those of previous studies [18,24,[36][37][38][39], including studies that have focused on urban GPs [40]. However, the current study indicated that many of these barriers appear to be more pronounced in rural versus urban contexts within Australia.…”
Section: Discussionsupporting
confidence: 85%
“…Few studies have specifically described rural/regional GPs' involvement and challenges in providing palliative and EOL care [24][25][26]. The current knowledge gaps have limited policy responses that might better support GPs in the delivery of this care in rural/regional settings.…”
Section: Introductionmentioning
confidence: 99%
“…This reconceptualization moves beyond the medical model of death and focuses on helping patients die at home and better quality of care in hospitals [24]. Recently, results of a systematic literature review illustrated that voices of rural participants at EOL have been marginalized and require attention because their needs are unique and present both challenges and benefits regarding the EOL experience in a rural setting [25]. Based on the results of this particular study, it is necessary for healthcare providers to understand the informational and medicinal needs of patients and family members in rural settings through communication and adequate dissemination of information [25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, results of a systematic literature review illustrated that voices of rural participants at EOL have been marginalized and require attention because their needs are unique and present both challenges and benefits regarding the EOL experience in a rural setting [25]. Based on the results of this particular study, it is necessary for healthcare providers to understand the informational and medicinal needs of patients and family members in rural settings through communication and adequate dissemination of information [25]. While there are diverse contexts for EOL, it has been has considered a taboo topic, difficult for healthcare participants to bring up and engage in conversation [26]; if family members and patients know that the EOL is approaching, they have the opportunity to have meaningful conversations that promote a good death [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation